To transform the equation −2y=14−6x to slope-intercept form, we need to isolate y on one side.
First, let's distribute the -2 on the right side:
-2y = 14 - 6x
Next, let's move the constant term to the right side by subtracting 14 from both sides:
-2y - 14 = -6x
Then, let's divide both sides of the equation by -2 to isolate y:
y = (6/2)x + 7
Finally, let's simplify the right side:
y = 3x + 7
Therefore, the equation −2y=14−6x in slope-intercept form is y = 3x + 7.
Transform the linear equation −2y=14−6x to slope-intercept form.
11 answers
wrong
Apologies for the mistake. Let's correct it:
To transform the equation −2y = 14 - 6x to slope-intercept form, we need to isolate y on one side.
First, let's divide both sides of the equation by -2 to isolate y:
-2y / -2 = (14 - 6x) / -2
Which simplifies to:
y = -7 + 3x
Therefore, the equation −2y = 14 - 6x in slope-intercept form is y = 3x - 7.
To transform the equation −2y = 14 - 6x to slope-intercept form, we need to isolate y on one side.
First, let's divide both sides of the equation by -2 to isolate y:
-2y / -2 = (14 - 6x) / -2
Which simplifies to:
y = -7 + 3x
Therefore, the equation −2y = 14 - 6x in slope-intercept form is y = 3x - 7.
Write 0.4x+0.2y=0.6 in slope-intercept form.(
To write the equation 0.4x + 0.2y = 0.6 in slope-intercept form, we need to isolate y on one side.
First, let's subtract 0.4x from both sides:
0.4x + 0.2y - 0.4x = 0.6 - 0.4x
This simplifies to:
0.2y = 0.6 - 0.4x
Next, let's divide both sides of the equation by 0.2 to isolate y:
0.2y / 0.2 = (0.6 - 0.4x) / 0.2
This further simplifies to:
y = 3 - 2x
Therefore, the equation 0.4x + 0.2y = 0.6 in slope-intercept form is y = -2x + 3.
First, let's subtract 0.4x from both sides:
0.4x + 0.2y - 0.4x = 0.6 - 0.4x
This simplifies to:
0.2y = 0.6 - 0.4x
Next, let's divide both sides of the equation by 0.2 to isolate y:
0.2y / 0.2 = (0.6 - 0.4x) / 0.2
This further simplifies to:
y = 3 - 2x
Therefore, the equation 0.4x + 0.2y = 0.6 in slope-intercept form is y = -2x + 3.
Write the linear equation 3y=6x−18 in slope-intercept form
To write the equation 3y = 6x - 18 in slope-intercept form, we need to isolate y on one side.
First, let's divide both sides of the equation by 3 to isolate y:
3y/3 = (6x - 18)/3
Which simplifies to:
y = 2x - 6
Therefore, the equation 3y = 6x - 18 in slope-intercept form is y = 2x - 6.
First, let's divide both sides of the equation by 3 to isolate y:
3y/3 = (6x - 18)/3
Which simplifies to:
y = 2x - 6
Therefore, the equation 3y = 6x - 18 in slope-intercept form is y = 2x - 6.
What is the slope and the y -intercept of the equation 9+27/2x=−3/2y . Write the y -intercept as an ordered pair.(1 point)
The slope is
. The y-intercept is (
)
The slope is
. The y-intercept is (
)
To determine the slope and y-intercept of the equation 9 + 27/2x = -3/2y, we need to rewrite it in slope-intercept form, y = mx + b.
First, let's isolate y by dividing both sides of the equation by -3/2:
(-3/2)y = 9 + 27/2x
y = -2/3 (9 + 27/2x)
To make it easier to identify the slope and y-intercept, let's simplify the equation:
y = -2/3 * 9 - 2/3 * 27/2x
y = -18 - 27x/3
y = -27x/3 - 18
y = -9x - 18
From this equation, we can see that the slope is -9 and the y-intercept is -18.
Therefore, the slope is -9 and the y-intercept is (-18, 0).
First, let's isolate y by dividing both sides of the equation by -3/2:
(-3/2)y = 9 + 27/2x
y = -2/3 (9 + 27/2x)
To make it easier to identify the slope and y-intercept, let's simplify the equation:
y = -2/3 * 9 - 2/3 * 27/2x
y = -18 - 27x/3
y = -27x/3 - 18
y = -9x - 18
From this equation, we can see that the slope is -9 and the y-intercept is -18.
Therefore, the slope is -9 and the y-intercept is (-18, 0).
the y-intercept is wrong
Apologies for the mistake. Let's correct it:
To determine the slope and y-intercept of the equation 9 + 27/2x = -3/2y, we need to rewrite it in slope-intercept form, y = mx + b.
First, let's isolate y by dividing both sides of the equation by -3/2:
(-3/2)y = 9 + 27/2x
y = (-2/3)(9 + 27/2x)
To make it easier to identify the slope and y-intercept, let's simplify the equation:
y = (-2/3)(9) - (2/3)(27/2x)
y = -6 - 9x/2
The y-intercept occurs when x = 0. Substituting x = 0 into the equation:
y = -6 - 9(0)/2
y = -6 - 0
y = -6
Therefore, the slope is -9/2 and the y-intercept is (-6, 0).
To determine the slope and y-intercept of the equation 9 + 27/2x = -3/2y, we need to rewrite it in slope-intercept form, y = mx + b.
First, let's isolate y by dividing both sides of the equation by -3/2:
(-3/2)y = 9 + 27/2x
y = (-2/3)(9 + 27/2x)
To make it easier to identify the slope and y-intercept, let's simplify the equation:
y = (-2/3)(9) - (2/3)(27/2x)
y = -6 - 9x/2
The y-intercept occurs when x = 0. Substituting x = 0 into the equation:
y = -6 - 9(0)/2
y = -6 - 0
y = -6
Therefore, the slope is -9/2 and the y-intercept is (-6, 0).